PRESERVATION OF FAMILY MEDICINE PLANTS (TOGA) TO IMPROVE COMMUNITY HEALTH IN GURAH VILLAGE IN THE MIDDLE OF PANDEMIC COVID-19 - Muharram, Muhammad; Kustiani, Edy (JMM - Jurnal Masyarakat Merdeka, 2021)
Limitation of Physical Interaction (Physical contact / physical distancing) during the COVID-19 pandemic has caused changes in the lifestyle or habits of the community, the economic crisis, and made health an expensive item. There is a fact that the level of community income has decreased due to social restrictions to break the chain of pandemic transmission COVID-19. Weak purchasing power and soaring prices for medicines have forced people to seek efforts to overcome this situation by looking back to nature. The use of traditional medicine for health maintenance and disease disorders is one of the things that is most likely to be done. Community service activities began with a survey on community understanding of family medicinal plants. The survey results showed 18.75% of the community knew the toga plant well. Then 43.75% of people have moderate knowledge. Meanwhile, 37.50% of people have a low level of knowledge about toga plants. Then carried out identification of medicinal plant species cultivated by the people of Gurah Village. The identification results showed 21 medicinal plants cultivated by the people of Gurah Village.Keywords: Medicinal Plants, COVID-19, Herbs